Plant protein diet suppressed immune function by inhibiting spiral valve intestinal mucosal barrier integrity, anti-oxidation, apoptosis, autophagy and proliferation responses in amur sturgeon (Acipenser schrenckii). Issue 94 (November 2019) - Wei, H.C.; Chen, P.; Liang, X.F.; Yu, H.H.; Wu, X.F.; Han, J.; Luo, L.; Gu, X.; Xue, M.
Abstract: An 8-week growth trial was conducted to investigate the effects of replacing dietary fishmeal with a plant protein blend on the growth performance, mucosal barrier integrity and the related regulation mechanism in Amur Sturgeon ( Acipenser schrenckii ) with initial weight of 87.48 g. Three isonitrogenous and isoenergetic diets were prepared. A basal diet containing 540 g/kg fishmeal (P0), whereas the other two diets were formulated by replacing 50% and 100% of FM with plant protein blend (soybean protein concentrate and cottonseed protein concentrate), and named as P50 and P100, respectively. Although essential amino acids, fatty acids, and available phosphorus had been balanced according to the nutrient requirement of sturgeon, compared with the fish of P0 and P50, the full plant protein diet (P100) significantly reduced growth performance and survival, and accompanied with serious spiral valve intestinal (SVI) damage. The increased tissue necrosis and failed responses in anti-oxidation, programming apoptosis, autophagy and cell proliferation system were regulated by inhibiting ERK1 phosphorylation, which indicated that SVI hypoimmunity and functional degradation were the main reasons for the high mortality and low utilization ability of plant protein in Amur sturgeon. Highlights: Plant protein (PP) substituted 50% fishmeal had no significant effects on the growth performance of Amur sturgeon. Full PP diet obviously reduced growth and survival of Amur sturgeon. PP diets induced spiral valve intestinal severe oxidative stress, mucosal barrier destruction and necrotic lesions. Anti-oxidation, apoptosis, autophagy and cell proliferation system were suppressed by inhibiting ERK1 phosphorylation. Hypoimmunity was the main reasons for the high mortality and low utilization ability of plant protein in Amur sturgeon.